Application of Satellite Monitoring Data for Winter Cereals Growing in the Lviv Region - Stupen, Mykhailo; Stupen, Nazar; Ryzhok, Zoriana; Stupen, Oksana (Geomatics and Environmental Engineering, 2020)
The authors applied satellite monitoring data of agricultural lands of the geographic information system of International Production Assessment Division of the United States Department of Agriculture on the example of winter cereal cultivation. The authors did so according to the indices of vegetation index NDVI, information on atmospheric precipitation, soil moisture, and air temperature compared to Earth observations to estimate the condition of their sowing area. According to the research results, one can use remote sensing data of the IPAD USDA geographic information system to monitor agricultural land, yield capacity prediction and the estimation of gross agricultural products.